Improvement of Centralized Routing and Scheduling Using Cross-Layer Design and Multi-Slot Assignment in Wimax Mesh Networks - Al-Humairi, Ali Zuhair Abdulameer (2009)
WiMAX (Worldwide Interoperability for Microwave Access) based wireless mesh network (WMN) aims to provide broadband wireless last-mile access. It is easy to deploy, has high speed data rate for large spanning area and is the key technology for the next generation wireless networking. The WiMAX mesh network is developed with the use of base station (BS) as the main controller for all the subscriber stations (SSs). This thesis proposes an optimized strategy namely cross-layer design in routing algorithms used find the best route for all SSs and scheduling algorithms, used to assign a time slot for each possible node transmission. The cross-layer design here is relying on the routing information in network layer and the scheduling in the medium access control (MAC) layer. This thesis also proposes a centralized scheduling algorithm that can avoid the collision by constructing routing path with multi-slot single transceiver system for WiMAX mesh networks. In our proposal, each node has one transceiver that can be tuned to any of the channels in the multi-slot assignment. The design parameters such as the number of the neighboring nodes, hop count to the BS, number of children per node, slot reuse, fairness, load balancing, quality of services (QoS) and node identifier (ID) are considered. Results of analysis show that the proposed algorithms significantly improve the system performance in the aspects of length of scheduling by 30.9%, channel utilization ratio (CUR) by 50.1%, throughput of the system by 49.7%, and the end to end average transmission delay by 56.7% as compared to the MC algorithm.